Study of Prevalence and Assessment of Knowledge, Attitude, and Beliefs of Cannabis Use in College Students - Lakhan Rudabhai Kataria; Nisheet Maheshkumar Patel; Dharmin K. Shah; Dhruv R. Raval; Jahnavi A. Bhatt (Annals of Indian Psychiatry)
Background: Cannabis is currently the most commonly used illicit drug and its use is increasing on college campuses in India. Students start cannabis use first time during college to heighten sociability and ease emotional distress from personal and academic problems, but its use can have a particularly negative impact on the lives of students. Aim: The aim of the study was to estimate prevalence and to assess the knowledge, attitude, and beliefs of cannabis use in college students. Settings and Design: This was a cross-sectional study. Methods: After obtaining necessary permissions, students from various medical and paramedical institutes from a central university were enrolled, data were collected through online Google Forms, and demographic details and other related information to estimate prevalence and assess knowledge regarding cannabis were asked. Attitude and beliefs were assessed with the Marijuana Effect Expectancy Questionnaire-Brief (MEEQ-B). Statistical Analysis: Descriptive and analytical (unpaired t-test) statistical methods using SPSS trial version 25 software were used. Results and Conclusion: Of 360 students, 41 students (prevalence: 11.4%) were cannabis users. For cannabis smokers versus nonsmokers, there is a statistically significant difference in mean scores of MEEQ-brief negative expectancies (P = 0.001), and it predicts that the nonsmokers would not initiate cannabis use in future compared to smokers who will have difficulty to reduce and stop cannabis use. To conclude, there is a lack of adequate knowledge, improper attitude, and misbeliefs regarding cannabis and its use in students. Hence, it is necessary to make students aware regarding the physiological and harmful effects of cannabis, so that increasing use of cannabis can be prevented.